Customer experience : future trends and insights - Shaw, Colin , 1958-; Dibeehi, Qaalfa; Walden, Steven (Palgrave Macmillan, 2010)
The quality of customer experience has become more important in recent times as businesses struggle to differentiate themselves. But what are the emerging trends that businesses should focus on today? The authors explore the growing trends that progressive businesses need to understand to give themselves a competitive advantage